PERBANDINGAN HUKUM PIDANA DALAM USAHA PEMBAHARUAN HUKUM PIDANA NASIONAL YANG BERKUALITAS - Aditya, Syafi’ Uddin; Sri Indrawati, A. A. (Kertha Semaya : Journal Ilmu Hukum, 2013)
The development of criminal law and criminal law reform efforts need to be supported by a comparative study. The comparative study of law is a very important and necessary for the legal and beneficial knowledge to better understand and develop their national criminal law. Therefore, this paper will describe the role and benefits of comparative criminal law for criminal law reform national.
Keywords: Comparative Law, Criminal Law Reform the National